2015
DOI: 10.1155/2015/751743
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between Phlegm Syndrome of Chinese Medicine and Coronary Angiography: A Systematic Review and Meta-Analysis

Abstract: Phlegm is one of the most common patterns of coronary artery disease (CAD) in Chinese medicine. Our research was aimed at investigating the association between phlegm syndrome of CAD and coronary angiography (CAG) by meta-analysis. According to inclusion criteria, a total of 30 studies involving 5,055 CAD patients were included. The meta-analysis showed that phlegm syndrome patients were prone to multivessel disease (28 studies, OR = 1.53, 95% CI, 1.24 to 1.88, P < 0.01) and higher Gensini score (2 studies, OR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Micro-circulation obstruction, abnormal haemorheology, unstable haemodynamics, abnormal platelet and endothelium, dysfunctional anticoagulation, and fibrinolysis: all conditions which lead to blood stasis [38]. Some studies proposed that possessing Stasis BC is significantly associated with hyperlipidaemia, atherosclerosis, coronary heart disease, or coronary artery disease [38][39][40]. Several studies demonstrated that olanzapine is a relatively unsafe drug, especially for patients who have coronary heart disease [41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…Micro-circulation obstruction, abnormal haemorheology, unstable haemodynamics, abnormal platelet and endothelium, dysfunctional anticoagulation, and fibrinolysis: all conditions which lead to blood stasis [38]. Some studies proposed that possessing Stasis BC is significantly associated with hyperlipidaemia, atherosclerosis, coronary heart disease, or coronary artery disease [38][39][40]. Several studies demonstrated that olanzapine is a relatively unsafe drug, especially for patients who have coronary heart disease [41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…Alzheimer's disease [42] Acne [40] AIDS, HIV infection [44] Alcoholism [43] Atopy/Eczema [40,53] Autism [41] Cancers [38] Celiac disease [26] Chronic fatigue and immune dysfunction syndrome [46] Chronic arthritis/pain treated with NSAIDs [47] Coronary heart disease [45] Crohn's disease [17] Cystic fibrosis [48] Dermatitis herpetiformis [49] Diabetes mellitus [33] Gastroenteritis [54] Inflammatory bowel disease [12] Irritable bowel syndrome [55,56] Nonalcoholic fatty liver disease [39] Obesity [33] Pancreatic dysfunction [50] Psoriasis [51] Rheumatoid arthritis [36] Schizophrenia [37] Urticaria [52] Ulcerative colitis [17] Alzheimer's disease (dementia) [57] Acne [58] AIDS, HIV infection [59] Asthma [60] Atopy [61] Autism [62] Bronchiectasis [63] Cancers [3] Celiac disease [64] Coronary heart disease [65] Coronary artery disease [66] Diabetes mellitus [67] Irritable bowel syndrome [64] Epilepsy [68] Hyperlipidemia [69] Hypertension…”
Section: Diseases Related To Increased Gi Barrier Permeability Diseasmentioning
confidence: 99%
“…Liver Qi stagnation also contributes to Phlegm production [3]. Phlegm is defined as a viscous and turbid pathological factor that is formed due to an imbalance in body fluid concentration and accumulates in certain parts of the body after condensation [3,66]. Phlegm can be released by the body (external or secretory form) in the form of sputum and nasal secretions from the respiratory tract, or it may be produced internally and may not be released (internal form) [89].…”
Section: What Is Phlegm Syndrome?mentioning
confidence: 99%
See 2 more Smart Citations